5x - 4y = 8
-24x + 4y = - 84-----ADD
- 19x = - 76
x = 4
24 - y = 21
y = 3
x = 4 , y = 3
2007-12-02 23:28:33
·
answer #1
·
answered by Como 7
·
1⤊
2⤋
I would use substitution to solve this. Though elimination method would work well also.
Solve the second equation for y:
y = 6x - 21
substitute for the y in the first equation:
5x - 4(6x - 21) = 8
5x - 24x + 84 = 8
-19x = - 76
x = 4
y = 3
2007-12-03 07:21:58
·
answer #2
·
answered by Marley K 7
·
1⤊
0⤋
Multiply the second equation by -4:
-24x + 4y = -84........(3)
Now add equation (1) and (3)
-19x = -76
x = 4
Substitute y with 4 in any equation (I will choose 1)
5 * 4 - 4y = 8
20 - 4y = 8
-4y = -12
y = 3
x = 4
y = 3
2007-12-03 07:22:27
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
5x-4y=8
6x-y=21
multiply each equation by 6 and then deduct i from ii.... You;ll get the value of y. Then place y value in either of the equations, you'll get value of x.
2007-12-03 07:22:22
·
answer #4
·
answered by ihrobin 5
·
0⤊
0⤋
Values of y:
5x - 4y = 8
4y = 5x - 8
y = (5x - 8)/4
6x - y = 21
y = 6x - 21
Value of x:
(5x - 8)/4 = 6x - 21
5x - 8 = 24x - 84
19x = 84 - 8
19x = 76
x = 4
Value of y:
y = (5(4) - 8)/4
y = (20 - 8)/4
y = 12/4
= 3
Answer: x = 4, y = 3
Proof:
6(4) - 3 = 21
24 - 3 = 21
2007-12-03 07:21:25
·
answer #5
·
answered by Jun Agruda 7
·
4⤊
1⤋
5x-4y=8
x=8,y=8
6x-y=21
x=4, y=3
2007-12-03 07:24:58
·
answer #6
·
answered by lm 4
·
0⤊
1⤋
5x-4y=8
24x-4y=84
19x=76
x=4
By the way which grade are you?
2007-12-03 07:21:27
·
answer #7
·
answered by ramesh_1960 3
·
1⤊
1⤋